Evaluación del desempeño de un nanocompuesto en las lechadas de cemento para la empresa Superior Energy Services a nivel laboratorio (2018)
It is the rheological and mechanical evaluation of a nanocomposite selected from a matrix method of selection applied in cement slurries of 16 ppg in order to analyze the performance and as a consequence the additional cost to be added in the unit costs of the prepared designs at the laboratory.